2006
DOI: 10.1111/j.1540-8167.2006.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Permanent Septal Versus Apical Right Ventricular Pacing: Short‐Term Results

Abstract: In contrast to RV apical pacing, chronic RV septal pacing preserved LVEF in patients with baseline LVEF < or = 45%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 18 publications
3
115
0
7
Order By: Relevance
“…21 -24 However, in patients with normal LV systolic function, ventricular synchrony may be of less importance. Victor et al 7 RV septal pacing preserved LVEF in patients with baseline LVEF ≤45%, but did not gain any advantage of LVEF in patients with baseline LVEF >45%. Sweeney and Hellkamp 25 showed that in patients with normal LV systolic function without myocardial infarction, the risk of heart failure after RVA pacing was low.…”
Section: Discussionmentioning
confidence: 98%
“…21 -24 However, in patients with normal LV systolic function, ventricular synchrony may be of less importance. Victor et al 7 RV septal pacing preserved LVEF in patients with baseline LVEF ≤45%, but did not gain any advantage of LVEF in patients with baseline LVEF >45%. Sweeney and Hellkamp 25 showed that in patients with normal LV systolic function without myocardial infarction, the risk of heart failure after RVA pacing was low.…”
Section: Discussionmentioning
confidence: 98%
“…A positive and statistically significant correlation was found between the paced QRS duration and global dyssynchrony (Victor et al, 2006;Flevari et al 2009;Takemoto et al, 2009;Muto et al, 2007). However, it has been shown in experimental studies that RV pacing sites maintaining an optimal LV function, are not correlated with the narrowest paced QRS complexes (Peschar et al, 2003).…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 86%
“…Pacing on the right ventricular (RV) septum, at high (septal RVOT pacing) (Giudici et al, 1997;Kolettis et al, 2000;Bourke et al, 2002;Tse et al, 2002;Dabrowska-Kugacka et al, 2009;Gong et al, 2009;Leong et al, 2010;Yoshikawa et al, 2010), mid (Yu et al, 2007;Cano et al, 2010;Muto et al, 2007) or lower (Flevari et al, 2009) septal pacing position has been introduced as a potentially favorable alternative to RVA pacing to preserve a more physiologic ventricular activation. Previous investigations of alternative pacing sites have yielded inconsistent results (Mera et al, 1999;Giudici et al, 1997;Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Tse et al Europace 2009;Victor et al, 1999) which may be attributable, in part, to the fact that the pacing site was determined on a topological rather than functional basis (Giudici & Karpawich, 1999). Many previous studies (Schwaab et al, 1999;Victor et al, 2006;Yu et al, 2007;Ng et al, 2009;Takemoto et al, 2009;Tse et al, Europace 2009, Gong et al, 2009Leong et al, 2010;Schwaab et al, 2001), have showed that septal pacing induced shorter paced QRS duration than RVA pacing did.…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 90%
See 2 more Smart Citations